2023
DOI: 10.1101/2023.05.03.539337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing Conformational Landscapes of Binding and Allostery in the SARS-CoV-2 Omicron Variant Complexes Using Microsecond Atomistic Simulations and Perturbation-Based Profiling Approaches: Hidden Role of Omicron Mutations as Modulators of Allosteric Signaling and Epistatic Relationships

Abstract: In this study, we systematically examine the conformational dynamics, binding and allosteric communications in the Omicron BA.1, BA.2, BA.3 and BA.4/BA.5 complexes with the ACE2 host receptor using molecular dynamics simulations and perturbation-based network profiling approaches. Microsecond atomistic simulations provided a detailed characterization of the conformational landscapes and revealed the increased thermodynamic stabilization of the BA.2 variant which is contrasted with the BA.4/BA.5 variants induci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…[120][121][122] These predictions may be relevant for the BA.2.86 RBD dynamic responses to binding in which variant-specific mutations may increase adaptability of the RBD loop and exploit the induced plasticity to boost immune evasion. The AF2 predictions are also consistent with our previous MD simulation studies of the Omicron RBD-ACE2 complexes, showing that the major structural differences between Omicron BQ.1 and XBB.1/XBB.1.5 RBD-ACE2 complexes are mostly confined to the fluctuations of the flexible loop regions 444-452 and 475-487 70,71 .…”
Section: Af2-based Atomistic Modeling and Prediction Of The Ba286 Rbd...supporting
confidence: 89%
See 1 more Smart Citation
“…[120][121][122] These predictions may be relevant for the BA.2.86 RBD dynamic responses to binding in which variant-specific mutations may increase adaptability of the RBD loop and exploit the induced plasticity to boost immune evasion. The AF2 predictions are also consistent with our previous MD simulation studies of the Omicron RBD-ACE2 complexes, showing that the major structural differences between Omicron BQ.1 and XBB.1/XBB.1.5 RBD-ACE2 complexes are mostly confined to the fluctuations of the flexible loop regions 444-452 and 475-487 70,71 .…”
Section: Af2-based Atomistic Modeling and Prediction Of The Ba286 Rbd...supporting
confidence: 89%
“…63,64 Our recent studies demonstrated that Omicron mutational sites can be dynamically coupled forming an adaptive allosteric network that controls balance and tradeoffs between conformational plasticity, protein stability, and functional adaptability. 65--69 We combined MD simulations and Markov state models to systematically characterize conformational landscapes and identify specific dynamic signatures of the early Omicron variants BA.1, BA.2, BA.3 and BA.4/BA.5 variants 70 and recent highly transmissible XBB.1, XBB.1.5, BQ.1, and BQ.1.1 Omicron variants and their complexes. 71 A significant number of computational studies emphasized the role of electrostatic interactions as a dominant thermodynamic force leading at binding of the S-protein with the ACE2 receptor and antibodies.…”
Section: Omicron Variantmentioning
confidence: 99%
“…S7). Notably, Verkhivker and co-workers (Verkhivker et al, 2023) identified a negative cross-correlated movement of these residues in the newer omicron spike variants upon ACE2 binding in the absence of heparin, while Kim and colleagues (Kim et al, 2023) showed that omicron spike interactions with HS and ACE2 are significantly enhanced compared to the Wuhan variant. Consistent with these and our findings, newer omicron spike variants could require HS to stabilize the protein:protein interface for subsequent steps in the infection process.…”
Section: Heparin Enhances the Open Spike Rbd:ace2 Interactions And Cr...mentioning
confidence: 99%
“…61 Integrative computational modeling approaches revealed that the S protein could function as an allosteric regulatory machinery controlled by stable allosteric hotspots acting as drives drivers and regulators of spike activity. [62][63][64][65][66][67] By combining atomistic simulations and a community-based network model of epistatic couplings we found that convergent Omicron mutations can display epistatic relationships with the major stability and binding affinity hotspots which may allow for the observed broad antibody resistance. 65 Analysis of conformational dynamics and allosteric communications in the Omicron BA.1, BA.2, BA.3 and BA.4/BA.5 complexes with the ACE2 host receptor characterized regions of epistatic couplings that are centered at the binding affinity hotspots N501Y and Q498R enabling accumulation of multiple Omicron immune escape mutations at other sites.…”
Section: Introductionmentioning
confidence: 97%
“…65 Analysis of conformational dynamics and allosteric communications in the Omicron BA.1, BA.2, BA.3 and BA.4/BA.5 complexes with the ACE2 host receptor characterized regions of epistatic couplings that are centered at the binding affinity hotspots N501Y and Q498R enabling accumulation of multiple Omicron immune escape mutations at other sites. 66 MD simulations and Markov state models systematically characterized conformational landscapes and identify specific dynamic signatures of Omicron variants and their complexes showing that convergent mutation sites could control evolution allosteric pockets through modulation of conformational plasticity in the flexible adaptable regions. 67 Recent computational studies suggested that Omicron mutations have variant-specific effect on conformational dynamics changes in the S protein including allosterically induced plasticity at the remote regions leading to the formation and evolution of druggable cryptic pockets.…”
Section: Introductionmentioning
confidence: 99%